PENILAIAN APLIKASI E-LKP MENGGUNAKAN PERSEPSI KARYAWAN (STUDI KASUS: UIN SYARIF HIDAYATULLAH JAKARTA) - Ditha Septiandani; A'ang Subiyakto; Evy Nurmiati (UIN Syarif Hidayatullah Jakarta, 2016)
The purpose of this study is to download yelidiki-variable relationship between the variables that influence the success of E-CGC system at UIN Syarif Hidayatullah an d also provide solutions and recommendations to the institution users to be taken into consideration for the development of the next system. The method used in this research is quantitative descriptive technique of non-random sampling for sample collection to be determined in advance as much as 66 respondents in the sample. The data obtained from these respondents further processed using statistical accounts PLS (Partial Least Square) with menggunkaan SmartPLS application. M odel to the success of the system that is used as a benchmark in this study is a model successive system proposed by DeLone and McLean (2003). The results of studies in which seven of the nine hypotheses received indicating that the application E-CGC implemented on employee and leader in UIN Syarif Hidayatullah runs almost in line with the depiction of the theory of information system success McL ean and DeLone. The existence of two relationships that are not confirmed in the study can be a space improvements for application development E-CGC. Researchers also recommend their attention on p there is an increase in customer satisfaction, because according to the model simplifications concluded from the study it appears that customer satisfaction is the most dominating factor in determining the success of the system in case of application of E-CGC at UIN Syarif Hidayatullah.